A novel recessive GUCY2D mutation causing cone–rod dystrophy and not Leber's congenital amaurosis - Ugur Iseri, Sibel A (Nature Publishing Group, 2010)
Cone–rod dystrophies are inherited retinal dystrophies that are characterized by progressive degeneration of cones and rods, causing an early decrease in central visual acuity and colour vision defects, followed by loss of peripheral vision in adolescence or early adult life. Both genetic and clinical heterogeneity are well known. In a family with autosomal recessive cone–rod dystrophy, genetic analyses comprising genome scan with microsatellite markers, fine mapping and candidate gene approach resulted in the identification of a homozygous missense GUCY2D mutation. This is the first GUCY2D mutation associated with autosomal recessive cone–rod dystrophy rather than Leber's congenital amaurosis (LCA), a severe disease leading to childhood blindness. This study hence establishes GUCY2D, which is a common cause for both recessive LCA and dominant cone–rod dystrophy, as a good candidate for autosomal recessive cone–rod dystrophy.